Multiculturalism in Children's Literature: A Study of a Collection of Poems by Elementary School Students in Yogyakarta - Anang Sudigdo; Onok Yayang Pamungkas (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Indonesia is a compound country that has multi-ethnic, ethnic, religious, and multi-cultural that stretch from Sabang to Merauke and from Miangas to Rote. Therefore, the introduction of multiculturalism needs to be given early on to students through literary literacy in writing poems charged with multiculturalism. This study aims to describe a collection of children's poems by elementary school students “Keragaman Budaya Indonesia” and “Sehimpun Puisi. Resep Membuat Jagat Raya” from the perspective of multiculturalism. This research uses the principles of the qualitative research paradigm with the content analysis method. The data in this study are the values of multiculturalism in children's poetry. The source of the data in this study is a collection of poems by elementary school students. Data analysis techniques use interactive analysis techniques, namely data reduction, data presentation, and verification. The results showed that in the poetry collection book there were fourteen indicators of multiculturalism, including respect for cultural equality, social class, ethnicity/ ethnicity, gender, language, religion, race, skin color, pluralism, equal rights, customs, behavior patterns, educational equality, and tolerance. The introduction of multiculturalism is used to teach students to respect each other and live in harmony and be free from prejudices of discrimination against religion, gender, race, culture, color, social class, educational equality, and student diversity.